A Measurement Method of Corrosion Rate in Condensate Pipeline Using Long Range Ultrasonic Test - Badri, Muftil; Ansukarto, Iswan; Puspito, Wismo (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2016)
The pipeline is one of the important means necessary as the transport medium of oil and gas, so that when the pipeline leak would greatly disrupt the production process. Pipelines generally use carbon steel, a major problem in the use of carbon steel is corrosion. Therefore, there must be serious action to prevent and simultaneously tackling the corrosion. In this study, the method used to measure the rate of corrosion is LRUT, this method is the latest technology in Indonesia in the field of inspection of corrosion rate. By using ultrasonic waves, this method will detect a reduction in the thickness of the pipe (wall loss), which is then used as the primary data to calculate the corrosion rate. The following conclusions were obtained: (1) Measurement of corrosion rate by using LRUT method can detect corrosion of the inner and outer walls of the pipe, the testing process faster, efficient and more extensive inspection area when compared with conventional methods. (2) The rate of corrosion on the circuit pipelines are not the same, it is in line with the magnitude of wall loss that occurs in a series of pipelines that are influenced by internal and external factors such pipes. (3) In general, a series of pipelines that have been tested using the method LRUT have decreased performance with a reduction in the thickness of the pipe wall. The greatest reduction in thickness occurs in TP # 02, anomaly number 13 with the corrosion rate of 0237 so that the estimated remaining life at that point was 19.49 years.